Сленгізми в жанрі інтернет-щоденника: функціонально- комунікативний аспект - Таран, Оксана; Taran, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті визначено жанрово-мовні особливості інтернет-щоденників, схарактеризовано тематику записів, обгрунтовано специфіку вияву автокомунікації. Моделювання жанру Інтернет-щоденника за методикою А. Вежбицької дозволило авторові статті виявити прагмакомунікативні умови функціонування сленгізмів у ньому.The article describes the genre and language features of Internet diaries, the characteristic of subjects is also given there. Based on M. Bakhtin’s idea of dialogic speech and Y. Lotman’s theory about two models of communication in the culture system , the author of the article defines the specificity of autocommunication in Internet diaries. The making model of Internet diary genre according to A. Wierzbicka methodology allowed to reveal such pragmatic and communicative conditions of slang words functioning, as following: 1) the aim for the addressee has probabilistic characteristic , the function of slang words in it is attracting attention; 2) a dominant in author self-presentation is emotive component, realized by slang words with emotive and evaluative connotation; 3) verbal slang words take part in the realization of the therapeutic function of Internet diary – they make dynamics of the emotional state ; 4) self-assertion and self-realization in desirable for the authorial «I» masks is the condition of verbal aggression, incarnated in slang words which are argots in origin.
Slang Words in the Internet Diaries Genre: Functional and Communicative Aspect
Keywords: інтернет-щоденник; автокомунікація; елементарний ілокутивний компонент; сленгізм; функція; Internet diary; autocommunication; elementary illocutionary component; slang word; function